MODEL EKONOMI DAGING SAPI DI INDONESIA - Sri Handayani (Jurnal Bisnis Tani, 2016)
Beef meat are the strategic commodities rapidly have demand increasing by years. Unbalanced on demand and supply effects on national demands performance, present by impressive rates of imported beef meats and the lifestock. This study aimed to analyze the economic model of beef in Indonesia. The data used in this study was secondary data on econometrical model approach, formulated from simultaneous equation. Model Sounding made by two stage least square (2SLS) method. The result shows domestic beef demand influenced by the imported price, chicken meat pric, national income and state population. Statistically, state population was significantly to beef meat demand. However, the status of domestic beef meat have been influenced by imported and domestic beef meat price and production, respectively, domestic demand and import of beef meat. Statistically, import price and import of beef meat were significant to domestic meat prices.